1989
DOI: 10.1111/j.1600-0722.1989.tb01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental root translucency as an indicator of age

Abstract: – The apical translucent zone was studied in 1000 human teeth. For each type of tooth, excluding molars, the size of the apical translucency was estimated according to the scoring methods of Gustafson (I), Dalitz (2) & Johanson (3). The lengths of the translucent zones were measured on moist and then on dry teeth, both unsectioned and sectioned, while the areas were measured on dry sectioned teeth only. Statistical analyses using the SPSS package in a Cyber computer indicated a symmetric distribution of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
4
19

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 14 publications
2
105
4
19
Order By: Relevance
“…We have found out that in pathological attrition the occlusal level of teeth lowers in a few times faster in dependence of forces that influence. Formation of reparative tertiary dentine, closing volume of pulp chamber and dystrophy processes take place in pulp structure that is unusual for physiological attrition [14][15][16][17][18][19][20]. Due to all these factors and principles we have approbated primary method of Kvaal et al age estimation technique and found modified regression formulas that approximate the calculation results with the real age.…”
Section: Introductionmentioning
confidence: 99%
“…We have found out that in pathological attrition the occlusal level of teeth lowers in a few times faster in dependence of forces that influence. Formation of reparative tertiary dentine, closing volume of pulp chamber and dystrophy processes take place in pulp structure that is unusual for physiological attrition [14][15][16][17][18][19][20]. Due to all these factors and principles we have approbated primary method of Kvaal et al age estimation technique and found modified regression formulas that approximate the calculation results with the real age.…”
Section: Introductionmentioning
confidence: 99%
“…Dişler, kimliklendir me çalışmalarında ağırlıklı olarak yaşın belirlenmesi ve ısırık izi analizleri için kullanılmıştır. Ayrıca, dişle rin sert yapıları ve düşük metabolizmaları nedeniyle, diş gelişim düzeninden alınan bilgilerin, organizmada ki diğer yapılara oranla en doğru sonuçları verdiği ile ri sürülmüştür (3,6,8,9,(11)(12)(13)(14)(15)(16).…”
Section: Introductionunclassified
“…Periodontal recession describe how much the roots of the teeth are exposed due to receding gums and is measured in millimetres (mm) by examining retraction of gums from root surface [11]. Root colour measures the degree of discoloration of the teeth which is related to increase in age ranging from a score of 1 referring to teeth with mild or no discoloration to a score of 5 referring to severely discoloured teeth [8]. …”
Section: The Datamentioning
confidence: 99%
“…These included periodontal recession, secondary dentin, apical translucency, root colour and root roughness of cementum. Periodontal recession, secondary dentin and apical translucency were measured using a seven point scoring system [5] whereas colour estimate and root roughness were measured using a five point scoring method [8].…”
Section: The Datamentioning
confidence: 99%